'Humans of New York' during the pandemic: Giving users a voice. Issue 2 (1st December 2021) - Roberts, Jessica
Issues of voice and representation have always been relevant in the media, but social media have raised new questions about the potential for more diverse, representative voices to appear in the media. Questions of representation are important in terms of the ability to cultivate empathy in the audience for the people represented. The contact hypothesis suggests that exposure to people through media may decrease prejudice for people perceived to belong to different groups. This article examines the pandemic-driven changes made to the Humans of New York social media project to determine the effect of a change in whose voice is privileged in this storytelling medium. This study compared quantitative calculations of engagement on Instagram as well as attempted to qualitatively analyse two sets of comments on posts to determine how this change in 'voice' affected the perception of and engagement with the posts and the people featured in them.